Is there a human right to be assisted in dying? [Temos um direito humano a ser assistido na morte?] - Tonetto, Milene (Princípios: Revista de Filosofia (UFRN), 2016)
This paper will focus on the issue of whether it is plausible to think about a human right to be assisted in dying. The right to be assisted in dying cannot be considered just a right of non-interference. It is better understood as a claim right because it demands assistance and positive actions. I will argue that the principles of individual autonomy and Kant’s notion of dignity taken independently cannot be considered plausible justification for the human right to be assisted in dying. Griffin’s personhood account points out that principles of liberty, minimum provision and autonomy must be taken together to justify human rights. Based on his theory, I will argue that a person with a terminal disease who was aware of her imminent death or who suffered from an intractable, incurable, irreversible disease may waive the right to life and choose death. Therefore, the right to life would not restrict the human right to be assisted in dying and a state that allowed the practice of assisted dying would not be disrespecting the human right to life. This article will defend that the personhood account is able to protect vulnerable people from making decisions under pressure and avoid the slippery slope objection.